PENYULUHAN MENGENAI PERBEDAAN PSIKOLOGI SUAMI-ISTRI - Jamalul Lail (UII, 2015)
Good and harmonious relationship between husband and wife does not just happen. It requires a great effort from both sides. In some cases, most of youngmarriage couples have not been able to understand deeply about the role and duties ofbeing marriage. Therefore, there should be education about the psychology of husbandand wife, especially in the dusun Sentono, which has a lot of young marriage couples.